Combination Effect of Engineered Endolysin EC340 With Antibiotics - Hong, Hye-Won; Kim, Young Deuk; Jang, Jaeyeon; Kim, Min Soo; Song, Miryoung; Myung, Heejoon (Frontiers in Microbiology, 2022)
Bacteriophage lysins, also known as endolysins or murein hydrolases, are hydrolytic enzymes produced by bacteriophages during the final stage of the lytic cycle to enable cleavage through the host’s cell wall, thus allowing the phages to burst out of their host bacteria after multiplication inside them. When applied externally to Gram-negative bacteria as recombinant proteins, lysins cannot easily reach the cell wall due to the presence of an outer membrane (OM). In this study, endolysin EC340 obtained from phage PBEC131 infecting Escherichia coli was engineered for improved OM permeability and increased activity against Gram-negative bacteria. The engineered endolysin, LNT113, was tested for potential synergistic effects with standard-of-care antibiotics. A synergistic effect was demonstrated with colistin, while an additive effect was seen with meropenem, tigecycline, chloramphenicol, azithromycin, and ciprofloxacin. Neither ceftazidime nor kanamycin showed any synergy or additive effects with the LNT113 endolysin. Moreover, synergy and additive effects could not be generalized by antibiotic class, OM traverse mechanism, molecular weight, or the bactericidal nature of each antibiotic tested.